The secret history of Audrey James : a novel - Marshall, Heather (Heather J.) (Ballantine, 2025)
"An astonishing historical novel of one woman's dangerous journey through World War II Germany and her life-changing friendship with a young woman decades later-from the #1 international bestselling author of Looking for Jane"--